2012
DOI: 10.1039/c2cp42628e
|View full text |Cite
|
Sign up to set email alerts
|

Final state distributions of methyl radical desorption from ketone photooxidation on TiO2(110)

Abstract: In this work, we report on product energy distributions for methyl radicals produced by UV photooxidation of a set of structurally related carbonyl molecules, R(CO)CH(3) (R = H, CH(3), C(2)H(5), C(6)H(5)), adsorbed on a TiO(2)(110) surface. Specifically, laser pump-probe techniques were used to measure the translational energy distributions of methyl radicals resulting from α-carbon bond cleavage induced by photoexcited charge carriers at the TiO(2) surface. Photoreaction requires the presence of co-adsorbed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(50 citation statements)
references
References 47 publications
(92 reference statements)
6
43
1
Order By: Relevance
“…Mass 15 only appears at short pump−probe delays consistent with the arrival time distribution of methyl radical photoproducts determined in an earlier study. 22 We also note that mass 26 (C 2 H 2 + ) and a small feature near mass 30 are also enhanced at shorter pump−probe delays. The latter suggests that their velocity distributions are more similar to the methyl product rather than the other C 2 H x + (mass 27−29) fragments whose relative intensities are comparable at both 25 and 60 μs pump−probe delays (see Figure 1).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Mass 15 only appears at short pump−probe delays consistent with the arrival time distribution of methyl radical photoproducts determined in an earlier study. 22 We also note that mass 26 (C 2 H 2 + ) and a small feature near mass 30 are also enhanced at shorter pump−probe delays. The latter suggests that their velocity distributions are more similar to the methyl product rather than the other C 2 H x + (mass 27−29) fragments whose relative intensities are comparable at both 25 and 60 μs pump−probe delays (see Figure 1).…”
Section: Resultsmentioning
confidence: 92%
“…The translational energies for the overall distribution, ⟨E t (total)⟩, and that for the "slow" and fast" channels, ⟨E t (slow)⟩ and ⟨E t (fast)⟩, are given in Table 2 along with those for the methyl radical loss channel determined in an earlier study. 22 The overall average translational energy obtained from the experimental data is small, ⟨E t ⟩ = 51 meV, which reflects the dominant contribution of the "slow" ethyl fragmentation channel, ⟨E t (slow)⟩ = 24 meV, relative to the "fast" channel, ⟨E t (fast)⟩ = 98 meV. Hence, the primary ethyl fragmentation process leads to photoproducts with low kinetic energies.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…25 Signal due to methyl radical is significantly larger at the shorter laser delay consistent with the higher average kinetic energy for the methyl radical ( E t (total) = 0.195 eV) compared to ethyl radical ( E t (total) = 0.051 eV) produced by 2-butanone photooxidation. 31 In addition to showing the product TOF-MS in Figs. 3(a) and 3(b), we have also included "4D" representations (which are functions of time, x pixel, y pixel, and signal intensity) of the data as recorded by the camera.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, recent work on ketone photooxidation has shown that acetaldehyde and acetone (along with co-adsorbed oxygen) photooxidize via methyl radical ejection. [40][41][42][43] In this paper, we have investigated the photooxidation of ethanol and 2-propanol under ultrahigh vacuum (UHV) conditions using a combination of temperature programmed desorption (TPD) measurements and time-of-flight mass spectrometry (TOF-MS) combined with state-resolved laser ionization of desorbing photoproducts. We present results which show that when these adsorbed alcohols are irradiated with ultraviolet light in the presence of oxygen at low temperature, methyl radicals are ejected into vacuum.…”
Section: Introductionmentioning
confidence: 99%